2019
DOI: 10.3390/molecules24244486
|View full text |Cite
|
Sign up to set email alerts
|

Housefly Pupae-Derived Antioxidant Peptides Exerting Neuroprotective Effects on Hydrogen Peroxide-Induced Oxidative Damage in PC12 Cells

Abstract: In this study, two antioxidant peptides were identified and characterized from the alcalase-hydrolysate of housefly (Musca domestica L.) pupae guided by ABTS cation radical scavenging activity. Peptides sequences were identified as DFTPVCTTELGR (DR12, 1338.48 Da) and ARFEELCSDLFR (AR12, 1485.66 Da) using nano-liquid chromatography-tandem mass spectrometry (LC-MS/MS). Both DR12 and AR12 exert strong ABTS cation radical scavenging ability with EC50 values of 0.39 and 0.35 mM, respectively. Moreover, AR12 can eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In another paper, two antioxidant peptides were obtained from the Alcalase hydrolysate of Arca subcrenata [373]. In another study, two antioxidant peptides (DFTPVCTTELGR and ARFEELCSDLFR) were purified from the Alcalase hydrolysate of housefly (Musca domestica L.) pupae [374]. They exhibited strong ABTS and cation radical scavenging activity with EC50 values of 0.39 and 0.35 mM, respectively [374].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In another paper, two antioxidant peptides were obtained from the Alcalase hydrolysate of Arca subcrenata [373]. In another study, two antioxidant peptides (DFTPVCTTELGR and ARFEELCSDLFR) were purified from the Alcalase hydrolysate of housefly (Musca domestica L.) pupae [374]. They exhibited strong ABTS and cation radical scavenging activity with EC50 values of 0.39 and 0.35 mM, respectively [374].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…pupae. The active peptides can effectively protect PC12 cells from oxidative damage induced by hydrogen peroxide by decreasing intracellular reactive oxygen species and malonaldehyde recovering cellular mitochondrial membrane potential and increasing the activity of intracellular superoxide dismutase guided by ABTS cation radical scavenging activity [ 34 ]. An antioxidant peptide derived from walnut meal protein and passed through gastrointestinal digestion displayed ABTS radical scavenging activity and ORAC assay also exhibited significantly protective effect on SH-SY5Y cells against oxidative damage [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is conjectured that fraction F4 with a lower molecular weight can more easily react with free radicals, converting them to more stable products and terminating the radical chain reactions. 25 Fig. 1b-d shows that fraction F4 displayed the best radical scavenging activity of all the fractions.…”
Section: Isolation and Purication Of The Sspmentioning
confidence: 92%
“…24 The natural antioxidant peptides from plants present benets, such as abundant raw materials, high efficiency, and safety. 25 Increasing evidence has suggested that the peptides found in plants inhibit oxidative stress by scavenging free radicals and increasing intracellular antioxidant enzyme activity and GSH levels. [26][27][28][29][30][31][32] Moreover, Zhang et al conrmed that Se and peptides have a synergistic effect, rendering Seenriched soybean peptides (SSP) desirable antioxidants.…”
Section: Introductionmentioning
confidence: 99%